Jurisprudential and Legal Reflection in Identifying Object of the Shares of Commercial Companies - S. Abd al-Muttalib Ahmadzadeh Bazaz; Morteza Muhammadi; Muhammad Reza Morvarid (آموزه‌‌های فقه مدني)
Understanding the nature of the shares of commercial companies has a great effect on correctly explaining the nature of their transactions and exchanges. Different perspectives have been presented in explaining the nature of shares. One of the most important views is the one that believes in object being or objectivity of the share right. According to this view, the rights that exist for the shareholder are reflected and embodied in the share sheet itself and become objective property. This view is in contrast to the view that considers the share as debt or the expression (explanatory) of chose in action. To prove the objectivity of the shares, several reasons have been cited, including the validity of the sale and the mortgage of the shares and the securities of the shares. In the present article, after explaining and criticizing the arguments cited in this view, while examining the view that the share is considered debt, an attempt has been made to prove that the share belongs to the category of “right” by reviewing the concept of property and its types, and considering the formation of a joint stock company.